Analysis of Factors Affecting Poverty in Eastern Indonesia - Saharuddin Didu; Tony S Chendrawan; An Nisaa Syauqi Ul Jannah (Tirtayasa Ekonomika, 2023)
Poverty is becoming one of the major problems in economic development especially in various developing countries. In this paper examines economic variables, such as foreign Direct Investment, minimum wage, Unemployment rate, Education, Communications Information Technology and Democracy in affecting Poverty in Eastern Indonesia. The use of a data panel model with fixed effect estimation for data of 7 Provinces from 2012 to 2019. Research results show that Foreign Direct Investment, Education and Democracy has a significant positive effect on Poverty. We also found that the minimum wage, unemployment rate and Communications Information Technology had a significant negative effect on Poverty. A further implication of this situation is that the increase that occurs in foreign capital investment, Education, and Democracy becomes a factor that leads to an increase in poverty in Eastern Indonesia. Meanwhile, the increase in the minimum wage variable, unemployment rate and Communication Information Technology can help to lower Poverty in East Indonesia. Thus, this paper will benefit policymakers of both the central and local governments to constantly pay attention to variables that can affect the increase in poverty in East Indonesia.